The Impact Of Innovative Human Resource Management Practices On Bank Employees’ Job Satisfaction And Job Performance In Malaysia: Perceived Union Support As A Moderator - Md Aris, Muhammad Zool Hilmi (2020)
This study examines the impact of innovative human resource management practices on employees’ job satisfaction conducted in local banks in Malaysia. This study also investigates the extent to which the role of perceived union support as a moderator between these two variables. This study highlights how far innovative human resource management practices affect employees’ job satisfaction in the organization. Human resource management practices include compensation, employee relations, performance appraisals, and human capital development. Employees’ job satisfaction is the dependent variable. The practice of innovative human resource management practices represented by compensation, employee relations, performance appraisal, and human capital development, are the independent variable; perceived union support is the moderator between these two variables. There are ten study hypotheses to unravel the influence of innovative human resource management practices on employees’ job satisfaction for this study. A total of 400 responses were collected from questionnaires distributed in the study areas. This study analyzed the data using SPSS version 23 and also PLS 3. Based on the results, there is a significant positive relationship between the independent (innovative human resource management practices) and dependent (employees’ job satisfaction) variables.